AB1180 Persistence Rate and Adherence Level to Allopurinol Among Patients with Gout Diagnosis and their Associated Determinants with Hypertensive Patients. (9th June 2015) - Perreault, S.; Nuevo, J.; Baumgartner, S.; Morlock, R.
Abstract : Background: Medication persistence and adherence are important factors to treatment success, particularly with diseases where target level achievement and maintenance are critical, as they are in gout. Identifying barriers to adherence provides opportunity to improve patient outcomes. Objectives: To evaluate the persistence rate and adherence level of allopurinol new users as well as their relation to patients' demographic and clinical characteristics. Methods: Among a large population-based cohort study, we assessed the profile of allopurinol use among new users of allopurinol after starting an antihypertensive agent. The cohort was built using RAMQ and MED-ECHO Québec administrative databases. A cohort of new allopurinol users aged 45-85 years who received ≥1 prescription between January 1997 and June 2007 were included. New users and patients with a ≥1 year gap in allopurinol use were defined as having no allopurinol prescribed in the 1 year preceding cohort entry. The cohort entry was defined by the date of the first allopurinol prescription. Drug adherence level was estimated using medication possession ratio (MPR). The cumulative persistence rate was estimated using a Kaplan-Meier analysis. Cox regression models were used to estimate the rate ratio of ceasing allopurinol after adjustment. Logistic regression models were used to establish the relation between non-adherence level and their determinants including patients having a prior use of allopurinol (gap of use >1 year). Results: Of the 2752 patients, mean (range) age was 70 (63-76) years, 82% were men, close to 50% had ≥1 cardiovascular disease, 33% had dyslipidemia, 21% had diabetes, 15% had chronic kidney disease, 6.3% had rheumatic disease, 21% were thiazides users, 33% were low-dose aspirin users, and 42% were NSAID users. During the 1st year, MPR was 71% and high level of adherence (MPR ≥80%) was 57%. Persistence decreased to 47% after 1-year follow-up (from 100% at time 0), and the proportion of patients who refilled allopurinol during the year after cessation ranged from 67%>71%. Patients having rheumatic disease and NSAIDs users are more likely to be non-persistent by 25% and 18%, respectively. In contrast, among previous allopurinol users (patients with ≥1 year gap in the use of allopurinol); persistence level was increased by 29%. Persistence was also higher among those using intra-articular corticosteroids (by 18%) and those who used ≥7 pharmacologic agents (39%). Determinants of non-adherence were similar to those of non-persistence. Conclusions: Barriers to persistence rate and adherence level occur early in the course of allopurinol therapy. Adherence is a key factor in determining the success of various therapeutic approaches, thus, greater attention should be paid to this aspect, which may result in improved patient outcome. Acknowledgements: This study was funded by AstraZeneca. Editorial support was provided by PAREXEL and funded by AstraZeneca. Disclosure of Interest: S. Perreault Grant/research support from: AstraZeneca, J. Nuevo Employee of: AstraZeneca, S. Baumgartner Employee of: Ardea Biosciences, Inc., a member of the AstraZeneca Group., R. Morlock Employee of: Ardea Biosciences, Inc., a member of the AstraZeneca Group.